Improving Learning Outcomes in Volleyball Games With Problem-Based Learning at SMAN 9 Pangkep - Muhammad Ahlil Akbar; Muh. Adnan Hudain; M. Sahib Saleh; Suwardi Suwardi; Nurul Musfira Amahoru (UNIVERSITAS NEGERI MAKASSAR, 2024)
The research aims to determine the improvement in learning outcomes for volleyball underpasses using the problem-based learning model at SMAN 9 Pangkep with a sample size of 33 (thirty-three) class XI students obtained through a purposive sampling technique using test equipment, namely knowledge tests and skills tests Passing below as a source of initial data and final research data. This research is classroom action research which consists of 4 stages, namely; (1) planning; (2) action; (3) observation; and (4) reflection using several cycles (pre-cycle and cycle I) to see student improvement after being given a learning model. problem-based learning. The results of the research showed that in the pre-cycle activities, the number of students who completed their studies was 7 students and 26 students did not complete their studies or 21% of students completed and 79% of students completed their studies. In cycle I there was a significant increase in student learning completeness to 33 students who completed or 100%. Conclusion: The problem-based learning model can improve the learning outcomes of volleyball underpassing for students at SMAN 9 Pangkep.